Overlobbying and Pareto-improving Agenda Constraint - Arnaud Dellis; Mandar Oak (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2017)
Policymakers face time and resource constraints in investigating issues and formulating policies. How do these constraints aect information transmission by informed but biased interest groups? We study this question using a model in which interest groups lobby a policymaker by oering veriÖable, policy-relevant information. The policymaker is limited in 1) his ability to verify or scrutinize the information oered by the interest groups (access constraint ), and 2) the number of issues he can reform (agenda constraint ). We show that when the policymaker faces an access constraint, but no agenda constraint, equilibrium lobbying by an interest group may signal its information only imperfectly. In particular, an interest group may lobby the policymaker even when it has unfavorable information, hoping that, due to the access constraint, the policymaker will not verify its information and, taking the costly act of lobbying as a signal of favorable information, reform its issue. We call such lobbying behavior ëoverlobbyingí. We show that imposing an agenda constraint can improve information transmission by curbing overlobbying. We identify circumstances in which an agenda constraint improves the ex ante expected welfare of the policymaker and of each interest group, thereby generating a Pareto improvement.
Keywords: D72; D78; D83; 330; Lobbying; information; access; agenda constraint; Pareto improvement